PERJANJIAN SEWA MENYEWA TOKO MILIK PEMERINTAH DAERAH DENGAN PEDAGANG PASAR ATAS (STUDI KASUS PADA KANTOR PENGELOLAAN PASAR KOTA BUKITTINGGI) - Rika Aryati (Ensiklopedia Sosial Review, 2022)
The Local Government of Bukittinggi City has determined trade and services as its superior potential by promoting and developing the people's economy by providing a place to trade, one of which is the shops in Pasar Atas. To obtain this facility, a shop rental agreement is required between the merchant and the government, but in reality, the socialization of this shop has not been maximized because many people do not know the procedure for renting the shop. This research is descriptive in nature with a sociological juridical approach. Descriptive means to describe data and information relating to the object under study. While the sociological juridical approach, meaning that the approach is carried out based on applicable laws and regulations and how it is applied in the field. The shop rental agreement between the local government and the tenant is carried out through several steps, namely an offer by the local government through an auction announcement, then acceptance by submitting an application letter. by the tenant candidate to the Mayor, as well as ratification of the agreement between the local government, namely the Bukittinggi Market Management Office and the tenant. The obligations of the parties in this agreement are to make advance payments, delivery of shop/rental rights, payment of rent, use of shops, provision of trash cans, fire extinguishers, payment of electricity bills by tenants and sale of lease rights. The problem encountered is that there is a delay in payment of rent by the tenant so that for every day of delay a fine is imposed until the rental permit is revoked.